Sigmoid colon obstruction due to Kaposiform Haemangioendothelioma - Tristan Anderson; Christopher Bourke; Roy Kimble (Elsevier, 2021)
Background: Kaposiform Haemangioendothelioma (KHE) is a very rare, benign but locally aggressive vascular tumour. Its incidence is 1/100000, and it is most commonly found in the cutaneous tissues of the extremities. Presentation: A 6-month-old presented acutely after 2 days of increasing abdominal distension. Apart from distension, clinical examination was unremarkable. An abdominal x-ray demonstrated massive gaseous distension of bowel loops. A contrast enema demonstrated an irregular stenosis within the sigmoid colon. An urgent laparotomy was performed. Management: A thick and very inflammatory stricture was resected. Histopathology confirmed this as Kaposiform Haemangioendothelioma with margin involvement. Patient had a complicated post-operative period due to prolonged sepsis resulting in a cardiac arrest and two return journeys to theatre. An MRI brain was performed after patient stabilisation, demonstrating bilateral cerebral infarcts - the patient went on to develop cerebral palsy. Discussion: Mainstay management of KHE is primary resection. It is associated with Kasabach-Merritt Phenomenon - a consumptive coagulopathy, which is present in 70% of KHE patients and has an associated 10% mortality rate. Conclusion: There are a small number of cases of KHE with gastrointestinal involvement in the literature. A number of these presented with bowel obstruction but no other had such a complicated post-operative course.